Stock price reaction to earnings announcements: evidence from the Colombo Stock Exchange, Sri Lanka / Rishan Sampath Hewage, Norashida Othman and Jaafar Pyeman - Hewage, Rishan Sampath; Othman, Norashida; Pyeman, Jaafar (2023)
This study investigates the reactions of stock prices to earnings announcements of the companies listed on the Colombo Stock Exchange (CSE), Sri Lanka. To verify the informational value of announcements, and possess market efficiency, the standard event study method was utilized. 158 companies were used to collect the data considering five years period, from 2015 to 2019. There were 334 earnings announcements for the sample period. Panel Ordinary Least Square analysis and the market model were used to estimate each company's expected and abnormal returns. The results indicated that investors react immediately and positively to good news announcements while negative reactions to bad news with lag reactions. Surprisingly, it could be noted that there was a sudden reaction in the market day before the good news announcement. Overall, there was a substantial price change of all the securities on the announcement day ignoring whether it is good news or bad news. This proves that earnings announcements possess informational value. Further, the share prices change on the event day shows that the market reacts immediately to the earnings information confirming that CSE follows a semi-strong form efficient hypothesis for earnings announcements. This is important for stakeholders to make investment decisions and financial decisions. Further, regulatory agencies need to build and implement rules and regulations in the market.